Associations between dementia diagnosis and end‐of‐life care utilization. Issue 10 (13th July 2022) - Luth, Elizabeth A.; Manful, Adoma; Prigerson, Holly G.; Xiang, Lingwei; Reich, Amanda; Semco, Robert; Weissman, Joel S.
Abstract: Background: Dementia is a leading cause of death for older adults and is more common among persons from racial/ethnic minoritized groups, who also tend to experience more intensive end‐of‐life care. This retrospective cohort study compared end‐of‐life care in persons with and without dementia and identified dementia's moderating effects on the relationship between race/ethnicity and end‐of‐life care. Methods: Administrative claims data for 463, 590 Medicare fee‐for‐service decedents from 2016 to 2018 were analyzed. Multivariable logistic and linear regression analyses examined the association of dementia with 5 intensive and 2 quality of life‐focused measures. Intensity measures included hospital admission, ICU admission, receipt of any of 5 intensive procedures (CPR, mechanical ventilation, intubation, dialysis initiation, and feeding tube insertion), hospital death, and Medicare expenditures (last 30 days of life). Quality of life measures included timely hospice care (>3 days before death) and days at home (last 6 months of life). Models were adjusted for demographic and clinical factors. Results: 54% of Medicare decedents were female, 85% non‐Hispanic White, 8% non‐Hispanic Black, and 4% Hispanic. Overall, 51% had a dementia diagnosis claim. In adjusted models, decedents with dementia had 16%–29% lower odds of receiving intensive services (AOR hospital death: 0.71, 95% CI: 0.70–0.72; AOR hospital admission: 0.84, 95% CI: 0.83–0.86). Patients with dementia had 45% higher odds of receiving timely hospice (AOR: 1.45, 95% CI: 1.42–1.47), but spent 0.74 fewer days at home (adjusted mean: −0.74, 95% CI: (−0.98)–(−0.49)). Compared to non‐Hispanic White individuals, persons from racial/ethnic minoritized groups were more likely to receive intensive services. This effect was more pronounced among persons with dementia. Conclusions: Although overall dementia was associated with fewer intensive services near death, beneficiaries from racial/ethnic groups minoritized with dementia experienced more intensive service use. Particular attention is needed to ensure care aligns with the needs and preferences of persons with dementia and from racial/ethnic minoritized groups.